Pengaruh Paparan Iklan dan Kelompok Referensi Terhadap Minat Beli - Adie Pamungkas; Hana Diana Maria; S. Sudianto; Firdan Gusmara Kusumah; Elvira Natasya Maulida (Universitas Warmadewa, 2024)
Advertising is still a powerful promotional medium today, where most aspects of the economy have shifted to online. In this digital era, conventional advertising, which is television advertising, is still an option and is still effective in business to use in promoting their products or brand campaigns. Apart from that, suggestions or recommendations from people around you can have an influence on someone when they make a decision to buy or consume a product. These two factors are combined and researched to find out their influence on purchasing interest from potential consumers. The population of this research is residents of the city of Tasikmalaya and the sampling method is judgment to select respondents to be studied. The results of this study indicate that advertising exposure and reference groups simultaneously and partially influences purchase intention.